Necrotizing Meningoencephalitis in a Captive Black and White Ruffed Lemur (Varecia variegata variegata) Caused by Acanthamoeba T4 Genotype. Issue 4 (November 2015) - Gaide, N.; Pelandakis, M.; Robveille, C.; Albaric, O.; Jouvion, G.; Souchon, M.; Risler, A.; Abadie, J.
Summary: A mature male, black and white ruffed lemur ( Varecia variegata variegata ) died in a zoological garden after a 4-day history of lethargy and non-responsive convulsions. Necropsy and histopathological examinations revealed acute necrotizing and haemorrhagic meningoencephalitis with intralesional amoebas confirmed by immunohistochemistry. Acanthamoeba T4 genotype was identified as the causative agent of the brain lesion, based on amplification and sequencing of 18S ribosomal RNA genes. The presence of free-living amoebas in water and mud from the lemur's environment was investigated by morphological and molecular analyses. The two predominant genera, representing 80% of isolated amoebas, were Naegleria spp. and Acanthamoeba spp. All Acanthamoeba isolates belonged to the T4 genotype. To the author's knowledge, this is the first report of a meningoencephalitis due to Acanthamoeba T4 genotype in Lemuridae with concurrent analysis of pathological tissues and environment.